Obesity among young Malaysians, is it an ASEAN lifestyle? - Rodriguez, Adriana Maria Ortega; Abdullah, Haslinda; Krauss, Steven Eric (Institute of Islam Hadhari, Universiti Kebangsaan Malaysia; together with Faculty of Human Ecology, Universiti Putra Malaysia; and Department of Islamic Development Malaysia, 2015)
For the past few decades, obesity became one of the most common chronic disorders among children and adolescents in the ASEAN region; and its prevalence continues to increase fast. This rapid increased obesity risks among young people can have detrimental effects on individual health and wellbeing and serious repercussions in terms of economic and social costs for developing society. This paper presents preliminary findings from a project on lifestyle, obesity and wellbeing among young people in Malaysia. The sample consisted of Malaysian secondary and university students and young workers (16 to 35 years old). The overall results indicate that 20.6% of the participants were overweight, 76.5 % were obese. The results also showed that male respondents exhibited higher BMI; spent more hours in physical activities and exercising, and engaged more in mood related eating behaviour than their female counter parts. Female participants were more weight conscious, relied more on their friends to avoid gaining weight and were more influenced by their friends eating attitudes and behaviour than the male participants. Furthermore, young people working exhibited higher BMI, reported less hours spent in physical activities and exercise during the week and weekends when compared with secondary and university school. Young worker also reported to be more weight conscious and influenced by their friends eating attitudes and behaviour more often than secondary school and university student. Secondary school student reported less frequently to eat their meals and/or snack while watching TV than did university student and young workers. These results suggest that the programs and policies designed to address increased risk of obesity among young people should be tailored to the appropriate gender and the current status of young Malaysians (i.e. secondary school, university students or young workers).